Analisis Pengaruh Brand Image dan E-Service Quality Terhadap E-Loyalty dengan E-Satisfaction sebagai Variabel Intervening Konsumen: Studi Kasus PT Lazada Indonesia - Tria Dyah Ayu Anggraeni (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The aim of this research is to analyze and test the influence of brand image and e-service quality on e-loyalty with e-satisfaction as an intervening variable in PT Lazada Indonesia's e-commerce. The population of this research is consumers from PT. Lazada Indonesia. With a known population, the Slovin formula was used with a total of 100 respondents in sampling. Data will be obtained using an online questionnaire via Google Form. The data analysis method used is associative statistical analysis and Partial Least Squares (SEM-PLS) analysis. The research results show that brand image has no effect on e-satisfaction, e-service quality using the dimensions of reliability, fullness and responsiveness has a positive and significant effect on e-satisfaction. Brand image has a positive and significant effect on e-loyalty, e-service quality using the dimensions of fullness and responsiveness has a positive and significant effect on e-loyalty, e-service quality using the reliability dimension has no effect on e-loyalty. E-Satisfaction has a positive and significant effect on E-Loyalty. E-Satisfaction does not play a role in mediating the brand image of E-Loyalty. E-Satisfaction plays a role in mediating the reliability of E-Loyalty. E-Satisfaction plays a role in mediating fulfillment of E-Loyalty. E-Satisfaction plays a role in mediating responsiveness towards E-Loyalty.